Exploring the role of brand communication on the end-users in the B2B luxury market : Hommés Studio case study - Brahem, Yasmine (My University, 2024)
This Master's thesis explores the role of brand communication on end-users in the B2B luxury market. It focuses on Hommés Studio, where I had a 720-hour internship within the studio’s Marketing department. This internship provided practical insights and real-world context for the findings. The primary objective is to investigate brand image continuity in a B2B2C context within the luxury sector. The study aims to uncover the various elements of brand communication in the B2B environment, analyze how brand image, values, and identity are transmitted, and propose strategies to enhance these communications. The research employs qualitative data, such as interviews and secondary data, and is finalized by a sentiment analysis to have different perspectives on brand communication and to achieve the objectives. Future research should expand the role of emerging technologies like AI and virtual reality in brand communication. By providing actionable recommendations, this thesis aims to bridge the gap between theory and practice, showing the importance of improving brand communication in the B2B luxury market. The insights from this research can be applied by companies like Hommés Studio to effectively convey their brand image and values to B2B clients and end-users.
Keywords: Brand communication; B2B; End-users; B2B2C; Luxury market